Comparative Genomics Reveals Two Major Bouts of Gene Retroposition Coinciding with Crucial Periods of Symbiodinium Evolution. (7th August 2017) - Song, Bo; Morse, David; Song, Yue; Fu, Yuan; Lin, Xin; Wang, Wenliang; Cheng, Shifeng; Chen, Wenbin; Liu, Xin; Lin, Senjie
Abstract: Gene retroposition is an important mechanism of genome evolution but the role it plays in dinoflagellates, a critical player in marine ecosystems, is not known. Until recently, when the genomes of two coral-symbiotic dinoflagellate genomes, Symbiodinium kawagutii and S. minutum, were released, it has not been possible to systematically study these retrogenes. Here we examine the abundant retrogenes (∼23% of the total genes) in these species. The hallmark of retrogenes in the genome is the presence of DCCGTAGCCATTTTGGCTCAAG, a spliced leader (DinoSL) constitutively trans -spliced to the 5′-end of all nucleus-encoded mRNAs. Although the retrogenes have often lost part of the 22-nt DinoSL, the putative promoter motif from the DinoSL, TTT(T/G), is consistently retained in the upstream region of these genes, providing an explanation for the high survival rate of retrogenes in dinoflagellates. Our analysis of DinoSL sequence divergence revealed two major bursts of retroposition in the evolutionary history of Symbiodinium, occurring at ∼60 and ∼6 Ma. Reconstruction of the evolutionary trajectory of the Symbiodinium genomes mapped these 2 times to the origin and rapid radiation of this dinoflagellate lineage, respectively. GO analysis revealed differential functional enrichment of the retrogenes between the two episodes, with a broad impact on transport in the first bout and more localized influence on symbiosis-related processes such as cell adhesion in the second bout. This study provides the first evidence of large-scale retroposition as a major mechanism of genome evolution for any organism and sheds light on evolution of coral symbiosis.